A Comparative Overview of the Livestock-Environment Interactions in Asia and Sub-saharan Africa - Otte, Joachim; Pica-Ciamarra, Ugo; Morzaria, Subhash (Frontiers in Veterinary Science, 2019)
This paper presents a comparative overview of the correlation between livestock and environment in Asia and Sub-Saharan Africa (SSA). Comparative analysis sharpens our capacity to understand issues by highlighting contrasts and similarities, thereby contributing to formulate and test hypotheses, develop theories and inform the decision-making process. The paper compares available information on the extent of grassland degradation, land and water pollution by nutrients and microorganisms, biodiversity loss and GHG emissions and their relation to livestock production in Asia and SSA. It then draws some lessons for sub-Saharan Africa (SSA) from Asia’s past livestock development trajectories, which suggest that forward-looking policies and programs that anticipate long-term changes in the livestock sector in SSA can support its sustainable development in the years ahead, from an environmental, social and public health perspective.